The impact of exchange rate changes on sectoral activity: The case of Egypt - Shokry, Nada (AUC Knowledge Fountain, 2017)
NOTE: A revised and corrected version, the version of record, is available online at: https://erf.org.eg/app/uploads/2018/11/1252.pdf This paper investigates the effect of changes in exchange rate on sectoral production in Egypt. For this purpose, the study, first, uses a MIDAS regression to compare between the sign and magnitude of the effect of two exchange rate measures on 22 subsectors and 4 aggregate sectors' production in the period between 1982 till 2014. One measure is the monthly deflated official bilateral exchange rate of EGP against the US dollar and the other is the annual real effective exchange rate of the EGP. The results show opposite signs and magnitudes when comparing both measures which is a highly important finding as the effect of exchange rate on production is a debatable topic where each study shows different results depending on many aspects including the choice of exchange rate measure. As the real effective exchange rate is more representative of a currency's real value, the interpretation of the estimation results is based on comparing public sectors and subsectors with private ones, export orientation with import orientation of each sector and sectors being tradable vs. non-tradable. Finally, results show that most of the low elasticity sectors are public, non-tradable and contribute by only little to GDP, while most tradable large sectors are highly elastic regardless of import and export shares of sectors.